Design and development of electric powered wheelchair model for navigation control / Afiqah Yaacob - Yaacob, Afiqah (2010)
This paper describes the significant design to build a wheelchair navigation based on joystick-controlled. This project is designed for particular purpose to increase the ease of mobility for disabled or golden ager especially those who hardly able to use both hand and legs for moving. The design would allow these people to not rely on others to move the wheelchair. A model of electrical powered wheelchair (EPW) moves according to the motion mode of a joystick operated by one person. The wheelchair model move when user moves the joystick according to any direction. The signal from joystick is converted to digital signal by Analogue to Digital Converter (ADC). This digital signal will enable the microcontroller to perform simple control algorithm to drive the DC motor to move forward or backward. During the movement, navigation system will be interrupted by the sonar range sensor. When the sensor detect hole on the pathway, the navigation system automatically avoid the hole by commanding backward operation. The user also will be alerted about the hole by the sound made by the buzzer. In addition to all the foregoing, the design of the system was compact and small thus suitable to be implemented into real wheelchair.